2010
DOI: 10.1177/1053451210378533
|View full text |Cite
|
Sign up to set email alerts
|

Dr. Richard J. Whelan: Seeing the Field of Emotional and Behavior Disorders Through the Lens of a Pioneer

Abstract: is a distinguished professor emeritus at the University of Kansas. His earliest professional experiences were at the Children's Hospital (Southard School) of the Menninger Clinic, where he served as a recreational therapist, teacher, and director of education. During his career at the University of Kansas and the KU Medical Center, he held an academic appointment in the Department of Psychiatry and was a professor of pediatrics, education, and special education. He also held the administrative posts of chairpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The videotapes were transcribed to print format and then edited and analyzed by the researchers. A more detailed description of the research methods can be found in the first report (Kaff et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The videotapes were transcribed to print format and then edited and analyzed by the researchers. A more detailed description of the research methods can be found in the first report (Kaff et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It’s hard to convince people to put that initial expenditure out there. (Kaff, Teagarden, & Zabel, 2011a, p. 188)…”
Section: Concerns About the Fieldmentioning
confidence: 99%
“…Richard Whelan expressed disappointment that the field has not focused more on early identification and prevention, “as Eli Bower wanted us to do in the 1950s. It just didn’t happen, much to the disappointment of many in our field” (Kaff et al, 2011a, p. 188).…”
Section: Concerns About the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…So those experiences were real gifts. Dick Whelan (Kaff, Teagarden, & Zabel, 2011a) from the University of Kansas. Dick was a member of the advisory committee for a large grant I had.…”
mentioning
confidence: 99%